Analysis of the Effect of E-Recruitment and Hybrid Working on Generation Z Job Application Interest with Work Motivation as an Intervening Variable: A Case Study of Gen Z Soloraya in Facing the World of Work. - Ikha Rani Yulianti; Irmawati Irmawati (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2026)
This study aims to analyze the influence of e-recruitment and hybrid work on job application interest among Generation Z, with work motivation as a mediating variable. The respondents in this study were 100 members of Generation Z in Soloraya, and the survey was conducted online using Google Forms. The sampling method used was purposive sampling. Validity and reliability testing used SmartPLS analysis. The analysis shows that e-recruitment does not have a significant effect on job application interest, whereas hybrid working does have a significant positive effect. In addition, e-recruitment and hybrid working have a significant effect on work motivation, and work motivation also positively affects job application interest. The results of this study also show that work motivation partially mediates the relationship between e-recruitment and hybrid working on job interest. These findings imply that organizations seeking to attract Generation Z should prioritize flexible work arrangements and enhance the motivational aspects of their digital recruitment systems. This study provides valuable insights for companies to design more appealing recruitment strategies aligned with the preferences and expectations of young job seekers.